Spontaneous hepaticoduodenal fistula of lithiasic origin - Perrone, Luis; Mazza, Milton; Ardao, Alberto R (Cirugía del Uruguay, 1973)
A patient presented an unusual variety of spontaneous bilio-digestive fistula of lithiasic origin between hepatic duct an duodenum. Preoperative diagnosis was established by filling bilio-digestive tract with barium through gastroduodenum.